Cutaneous manifestations of dermatomyositis in male patient: a rare report - Ganesh Dhavalshankh; Archana Dhavalshankh; Vaishali Masvekar (Our Dermatology Online, 2013)
Introduction: Dermatomyositis is an idiopathic inflammatory myopathy. It is a systemic disorder that most frequently affects the skin and muscles, but may also affect the joints, the esophagus, the lungs, and, less commonly, the heart.Case report: It is presented with characteristic cutaneous findings like skin rash as well as progressive symmetrical proximal muscle weakness. Its prevalence rate is approximately one per 100,000 in the general population with a female to male predominance of about 2:1.Conclusion: We report a male patient with the classical features of dermatomyositis in whom cutaneous changes preceded muscle weakness.